2001
DOI: 10.1016/s0927-538x(01)00020-8
|View full text |Cite
|
Sign up to set email alerts
|

Selecting macroeconomic variables as explanatory factors of emerging stock market returns

Abstract: Emerging stock markets have been identified as being at least partially segmented from global capital markets. As a consequence, it has been argued that local risk factors rather than world risk factors are the primary source of equity return variation in these markets. This paper seeks to address the question of whether macroeconomic variables may proxy for local risk sources. We find moderate evidence to support this hypothesis. Further, we investigate the degree of commonality in exposures across emerging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
129
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(148 citation statements)
references
References 59 publications
15
129
1
3
Order By: Relevance
“…The inclusion of output and interest rates is consistent with existing Australian work; see Bilson, Brailsford, and Hooper (2001), Groenewold (1997, 2001), and Ragunathan, Faff, and Brooks (1999). The inclusion of other variables may also be desirable at some point; for example Faff and Brailsford (1999) found that oil prices have effects over a broad range of sectors.…”
Section: A Svar Model Of Real Equity Pricessupporting
confidence: 71%
“…The inclusion of output and interest rates is consistent with existing Australian work; see Bilson, Brailsford, and Hooper (2001), Groenewold (1997, 2001), and Ragunathan, Faff, and Brooks (1999). The inclusion of other variables may also be desirable at some point; for example Faff and Brailsford (1999) found that oil prices have effects over a broad range of sectors.…”
Section: A Svar Model Of Real Equity Pricessupporting
confidence: 71%
“…Such estimation would mean ignoring the effect of changes in unanticipated components of local and global variables on country risk and therefore could be misleading. To overcome such potential problem of misspecification, we follow the approach of Gangemi et al (2000), Bilson et al (2001), Singh (1993) and Tan (1992) and compute residuals from ARIMA models fitted to each independent variable. Another advantage of using the unexpected components of the variables is that the potential problem of multicollinearity is minimized.…”
Section: Data and Econometric Methodologymentioning
confidence: 99%
“…Numerous studies have modeled the relationship between equity market returns and risk factors in terms of production rates, productivity, gross national product growth rate, unemployment, yield spread, interest rates, inflation, dividend yields and other local factors (Fama, 1970;Chen, Roll, & Ross, 1986;Jorion, 1991;Groenewold & Fraser, 1997;Ely & Robinson, 1997;Kwon & Shin, 1999;Serra, 2000). Our guidance on the selection of local and global factors comes from Bilson, Brailsford, and Hooper (2001) and Ferson and Harvey (1994) respectively. Bilson et al (2001), find that domestic money supply, goods prices, real activity, and exchange rates are significant in their association with emerging equity returns.…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…As underlined by Bilson et al (2001), the selection of variables lends itself to criticism due to the subjectivity and arbitrariness involved in this process. In this paper, the selection of relevant variables is based on three criteria.…”
Section: Variable Selection Criteriamentioning
confidence: 99%